An Imperfect Integrated Production with Advertisement Cost Due to PMC under Fuzzy Systems - Kuppulakshmi, V.; Sugapriya, C. (International Journal of Psychosocial Rehabilitation, 2020)
The development of imperfect production setup in fuzzy system is proposed in the paper. The demand function is treated as exponential together with inventory. The outcome of the paper mainly concentrates on reducing the total price of the production cycle as the number of cycles increases, this result is compared with the fuzzy environment by using the pentagonal fuzzy number and the graded mean difference method is adopted for defuzzification of the result. Eventually, numerical illustrations are provided for comparing the total cost of the model introduced and the logical analysis are carried out for analyzing the impact of parameter variation on the decision variables.